Impact of titanium dioxide nanoparticles (TiO2-NPs) on growth_x000D_ and mineral nutrient uptake of wheat (Triticum vulgare L.) - (:unkn) unknown (My University, 2020)
Titanium dioxide nanoparticles (TiO2-NPs) among metallic NPs are one of the mostproduced and consumed NPs in the world. Thus, TiO2-NPs release into the environmentis inevitable. Their impact on food source cereals is still unclear. The purpose of thisstudy was to assess the phytotoxic impacts of TiO2-NPs on growth and some mineralnutrient (zinc (Zn), iron (Fe), manganese (Mn), copper (Cu), nitrogen (N), phosphorous(P), potassium (K)) uptake of the wheat (Triticum vulgare L.) plant. The TiO2-NPsuspensions at increasing concentrations (0, 5, 10, 20 and 40 mg L-1) were applied towheat plant Yunus cultivar grown in hydroponic culture under controlled conditions for21 days. The results indicate that the TiO2-NPs have not statistically significant effectson plant growth. The chlorophyll content was decreased with increasing TiO2-NPtreatment, except for 5 mg L-1 TiO2-NPs treatment. The higher N (4.58%), P (0.78%), Zn(87.50 mg kg-1), and Cu (12.90 mg kg-1) concentration were recorded at 40 mg L-1 TiO2-NPs treatment. On the other hand, K concentration was decreased at 20 and 40 mg L-1TiO2-NPs treatments. This study has shown that exposure to TiO2-NPs causes nosignificant phytotoxic effect on wheat.